The intersection of food insecurity and child health: Implications for policy and practice in the Bronx - Lily Lee; Fatoumata Diallo; Lauren J. Shiman (PLoS ONE, 2025)
Background Food insecurity, a significant stressor for many US families and children, is strongly associated with poverty and increases the risk of adverse physical and mental health outcomes. Communities like the Bronx, disproportionately affected by the COVID-19 pandemic due to job losses and increased reliance on emergency food resources, experience heightened food insecurity and face increased risk of various health conditions, such as asthma. This study aims to investigate the relationship between household food insecurity risk and child health outcomes in the Bronx. Methods A cross-sectional analysis was conducted using data from the 2021 NYC KIDS, a population-based sample of households with children aged 1–13 years. A total of 1646 households residing in the Bronx were included in the analysis. Descriptive statistics and weighted multivariable logistic regression models were employed to examine the association between food insecurity risk and specified childhood health outcomes. Results The study revealed a high prevalence of food insecurity risk among children in the Bronx, with over half residing in food-insecure households (58.5%). Household food insecurity risk was significantly associated with increased odds of overweight or obesity (adjusted OR: 1.58, 95% CI:1.01–2.47), as well as mental health disorders such as anxiety, depression, adjustment disorders, and learning disorders. Discussion These findings underscore the critical need for increased investment in food assistance programs within the Bronx. Despite government assistance efforts, various factors exacerbate food insecurity, including policy changes, disruptions in the supply chain, and elevated food prices. Innovative approaches such as baby bonds, prescription produce programs, paid family leave, child tax credit and guaranteed basic income should be considered to address these limitations and enhance food security in the Bronx. Conclusion This study provides important insights into the association between household food insecurity risk and child health outcomes in urban, low-income communities, emphasizing the need for targeted interventions to address food insecurity and promote health equity among vulnerable children.